CD4 expression on monocytes correlates with recovery from multiple organ dysfunction syndrome and mortality in patients with septic shock - Sun, Yingqian; Lu, Yan; Xing, Rui; Zhang, Yongjun; Zhang, Longyi (Frontiers in Medicine, 2024)
Background To date, the correlation between CD4 on the monocytes (mCD4) expression and the prognosis of patients with septic shock remains unclear. The purpose of this study was to analyze the expression of mCD4 in these patients and further evaluate whether mCD4 expression correlates with either the recovery from multiple organ dysfunction syndrome (MODS) or mortality. Methods The study participants were recruited from a tertiary general hospital in China (Affiliated Dongyang Hospital of Wenzhou Medical University). Sepsis and septic shock were diagnosed based on the diagnostic criteria of Sepsis-3. MODS was defined as a Sequential Organ Failure Assessment score of at least two organ systems ≥2. Persistent MODS was defined as the continual meeting of the MODS criteria when re-evaluated one week after admission (day 7). A logistic regression model was used to test whether mCD4 was an independent prognostic factor for mortality in patients with septic shock. A paired sample rank sum test was used to examine the correlation between mCD4 expression and MODS recovery. Result The study recruited 79 patients with septic shock as the study group, 74 patients with sepsis as the disease control group, and 56 volunteers as healthy controls. In the first 24 h after admission (day 1), mCD4 expression was significantly reduced in patients with septic shock compared to healthy controls and patients with sepsis. Moreover, mCD4 expression was an independent prognostic factor for in-hospital and 28 day mortality in patients with septic shock. mCD4 expression did not show significant differences in patients with persistent MODS on day 7 compared to day 1. However, mCD4 expression was significantly higher in patients without persistent MODS on day 7 than on day 1. Conclusion mCD4 expression is significantly reduced in patients with septic shock, which is an independent prognostic factor for mortality and closely related to recovery from MODS.